Primary Health Care Services During Pandemic - Hijriyati Nurfaiza; Dedy Purwito (UM Purwokerto Press, 2022)
The COVID-19 in early 2020 greatly impacted to the health care system, forced patients to change their use of health services during the pandemic. Indonesia Primary health care (Puskesmas) is the frontline in health development including health services. In order to services provide and adopt the situation and response to the pandemic, there are several changes to anticipate the potential for a resurgence of cases. Objective of this study was to find out the Puseksmas services. A qualitative research with phenomenological methods carried out using interviews, observation, FGD, and documentation. Data reduction, data display, and verification as well as drawing conclusions made for analyze the phenomena. The study results have obtained four themes; 1) digital health care services, 2) Health Protocol Requirement, 3) The Task Force, 4) Herd Community Effort. Puskesmas should continue the services and make an innovative for health care services to the individual and community.